2011
DOI: 10.1037/a0022593
|View full text |Cite
|
Sign up to set email alerts
|

Smiles make it easier and so do frowns: Masked affective stimuli influence mental effort.

Abstract: Two experiments tested the hypothesis that exposure to masked emotional expressions during the performance of cognitive tasks influences effort mobilization. In support of the predictions, participants who processed masked sad faces during task performance under "do your best" instructions showed stronger sympathetic nervous system discharge to the heart (shorter pre-ejection period, higher systolic blood pressure) than participants who were exposed to masked smiling faces or angry faces. Assessed task apprais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
70
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(90 citation statements)
references
References 60 publications
17
70
3
Order By: Relevance
“…Several studies have supported this systematic impact of implicitly processed affect primes on effort-related cardiovascular response in cognitive tasks (e.g., Chatelain and Gendolla, 2015;Gendolla and Silvestrini, 2011;Lasauskaite et al, 2013). The present research applied a similar logic to explain how the aging stereotype can influence effort mobilization.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Several studies have supported this systematic impact of implicitly processed affect primes on effort-related cardiovascular response in cognitive tasks (e.g., Chatelain and Gendolla, 2015;Gendolla and Silvestrini, 2011;Lasauskaite et al, 2013). The present research applied a similar logic to explain how the aging stereotype can influence effort mobilization.…”
Section: Introductionsupporting
confidence: 53%
“…Also in our previous studies on affect priming, we have only sometimes found prime effects on subjective demand ratings (e.g., Gendolla and Silvestrini, 2011;Lasauskaite et al 2013, Lasauskaite Schüpbach et al, 2014Silvestrini and Gendolla, 2011b), or subjective effort (e.g., Chatelain and Gendolla, 2015). Other studies revealed the expected effort effects without significant effects on these self-report measures (e.g., .…”
Section: Discussionmentioning
confidence: 67%
“…Implicit emotional primes are thought to automatically activate mental representations determining the subjective experience associated with task demands. For example, implicit sadness primes promotes the subjective experience of task difficulty, while happiness primes are associated with ease (Gendolla and Silvestrini, 2011;Silvestrini and Gendolla, 2011b). Together, these studies support the general premise that action-inaction concepts and emotional signals can encourage goal pursuit and modulate effort exertion.…”
Section: Introductionsupporting
confidence: 58%
“…Positive subliminal cues are thought to decrease the perceived difficulty of a task and consequently reduce effort mobilization (Niedenthal, 2008;Gendolla and Silvestrini, 2011;Silvestrini and Gendolla, 2011;Gendolla, 2012), which may result in decreased performance (Zemack-Rugar et al, 2007). Positive subliminal cues represent a sign that goal pursuit is easy and induce coasting.…”
Section: Introductionmentioning
confidence: 99%